Li Hui: From a Nightclub to Eternity - Phil Zheng Cai (Oz, 2018)
The connection between authenticity and Hui’s work can be traced to his understanding of fine art creation in relation to religions. he believes the ability to create is exclusively anthropic. He argues that artists are playing more of a role to replace God in what they create, they invent, and influence. This is the pinnacle of authenticity.